1997
DOI: 10.1182/blood.v90.7.2819.2819_2819_2825
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Interactions Between Hb α-G Philadelphia, HbC, and HbS: Phenotypic Implications for SC α-G Philadelphia Disease

Abstract: We show here that αG-Phila.2βC2 has an increased rate of crystal nucleation compared to α2 βC2 (HbC). We conclude from this finding that position α68, the mutation site of αG-Phila.2 β2 (HbGPhiladelphia), is a contact site in the crystal of HbC. In addition, that HbS enhances HbC crystallization (additive to the effect of αG-Phila, as shown here) and that αG-Phila. inhibits polymerization of HbS are pathogenically relevant previously known facts. All of these findings help explain the phenotype of an individua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2002
2002
2002
2002

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…More recently, we have observed that little or no pathology arises in compound heterozygous patients of HbC, including SC compound heterozygotes, that also express hemoglobins shown to increase the nucleation kinetics of liganded HbC crystallization (Nagel et al, 1993;Lawrence et al, 1997). These studies have also served in the identi®cation of some residues involved in the intermolecular contacts of the crystal (Hirsch et al, 1988(Hirsch et al, , 1998Hirsch, Witkowska et al, 1997;Hirsch, Rybicki et al, 1997;Lin et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, we have observed that little or no pathology arises in compound heterozygous patients of HbC, including SC compound heterozygotes, that also express hemoglobins shown to increase the nucleation kinetics of liganded HbC crystallization (Nagel et al, 1993;Lawrence et al, 1997). These studies have also served in the identi®cation of some residues involved in the intermolecular contacts of the crystal (Hirsch et al, 1988(Hirsch et al, , 1998Hirsch, Witkowska et al, 1997;Hirsch, Rybicki et al, 1997;Lin et al, 1989).…”
Section: Introductionmentioning
confidence: 99%